A multi-criteria framework for the holistic ergonomic design evaluation of VR products - Akgun Tokatli (Frontiers in Virtual Reality)
The rapid advancement of virtual reality technology has significantly influenced technological, social, and business sectors. In Virtual Reality (VR) product design and development, the prioritisation and optimization of ergonomic criteria are crucial for shaping product decisions and fostering innovation. Ergonomics encompasses several sub-dimensions, making product design a complex, multi-criteria decision-making process. In this context, decisions are typically made based on collective insights and data gathered by the development team. The Analytic Hierarchy Process (AHP) is widely used to understand the prioritisation of multiple criteria. Study aims to analyse the impact and relationship between the prioritisation of ergonomic criteria by VR design and development teams on product value and innovation propositions and to present an approach for ergonomics-based product differentiation and innovation analysis. Through an extensive literature review and expert interviews, 11 specific ergonomic criteria were identified. These criteria were then assessed by practitioners using the AHP methodology, enabling pairwise comparisons to determine their relative importance. The analysis explored the differences between teams that conduct user research and those that do not. The study provides insights into ergonomic priorities in VR product design and development. The results were compared with the value propositions highlighted on the websites of 20 companies producing non-gaming VR products. As expected, the comparison showed that the ergonomic criteria emphasised in marketing coincided with those prioritised by the participants, especially among those who conducted user research. It shows that this scientifically proven agile approach can be used to find points of differentiation in the product development and innovation. Marketing value propositions can be used to identify which ergonomics criteria are prioritised by the market or by specific products. These criteria are compared by determining how the product team’s mental model prioritises them and a gap and alignment analysis can be performed according to the product purpose and findings support ergonomics-based decision making and innovation.